1986
DOI: 10.1038/jcbfm.1986.53
|View full text |Cite
|
Sign up to set email alerts
|

Regional Blood—Brain Glucose Transfer in the Rat: A Novel Double-Membrane Kinetic Analysis

Abstract: Summary: Regional blood-brain glucose transfer was studied in pentobarbitone-anaesthetized rats using a pro grammed intravenous infusion technique that maintained steady levels of unlabeled (up to 55 mM) and tracer n-glucose in the circulating plasma. Regional cerebral blood flow, glucose phosphorylation rate, and tissue glu cose content were also measured under comparable con ditions. Data were analysed in terms of irreversible Mi chaelis -Menten kinetics assuming independent influx and efflux (Type I) and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 26 publications
0
48
2
Order By: Relevance
“…3, the essential difference is that the individual fluxes J in and J out are reversible. It has been shown (Cunningham et al, 1986;Gruetter et al, 1998;Mahler and Cordes, 1971) that this change amounts to replacing the Michaelis-Menten constant K m with a product dependent term K m + [Glc]. This can be interpreted as a product-inhibited Michaelis-Menten model, in which, for instance, the forward reaction (uptake of glucose) is inhibited when brain glucose is present.…”
Section: Kinetic Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…3, the essential difference is that the individual fluxes J in and J out are reversible. It has been shown (Cunningham et al, 1986;Gruetter et al, 1998;Mahler and Cordes, 1971) that this change amounts to replacing the Michaelis-Menten constant K m with a product dependent term K m + [Glc]. This can be interpreted as a product-inhibited Michaelis-Menten model, in which, for instance, the forward reaction (uptake of glucose) is inhibited when brain glucose is present.…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…Recently, Gruetter et al (1998) proposed describing glucose transport kinetics across the human blood-brain barrier by a reversible Michaelis-Menten model (Cunningham et al, 1986;Mahler and Cordes, 1971). Although the model can also be visualized by Eq.…”
Section: Kinetic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was generally accepted that blood-to-brain influx, and brain-toblood efflux of glucose were equal (or symmetrical). 49 -52 Cunningham et al 51 considered the possibility that BBB glucose transport could be kinetically analyzed in terms of translocation through a single membrane, or alternatively via individually (asymmetric) luminal and abluminal membranes. From these double-membrane mathematical analyses of brain glucose transport in modulated states (wherein anesthetized and conscious animals, or control and kainate-treated rats were compared) asymmetric distributions of capillary glucose transporter were predicted.…”
Section: Polarity Of the Brain Microvasculaturementioning
confidence: 99%
“…From these double-membrane mathematical analyses of brain glucose transport in modulated states (wherein anesthetized and conscious animals, or control and kainate-treated rats were compared) asymmetric distributions of capillary glucose transporter were predicted. 48,51,53 Immunogold electron microscopic studies, using antisera to the GLUT1 glucose transporter, were used to study the subcellular distribution of transporter protein in the BBB. 17,54 -56 In dog brain capillaries, Gerhart et al 54 observed a symmetrical distribution of GLUT1 epitopes between the luminal and abluminal membranes.…”
Section: Polarity Of the Brain Microvasculaturementioning
confidence: 99%